Trichothecene genotypes, chemotypes and zearalenone production by Fusarium graminearum species complex strains causing Fusarium head blight in Argentina during an epidemic and non-epidemic season - Yerkovich, Nadia (2017)
Members of Fusarium graminearum species complex are the main pathogens associated with Fusarium head blight (FHB) in wheat in Argentina, which produce trichothecene mycotoxins that are found in wheat grain and by-products. The aim of this study was to determine the chemotype and trichothecene genotypes of Fusarium graminearum species complex strains isolated from wheat in Argentina during an epidemic and a non-epidemic harvest season. A total of 115 and 108 strains obtained from wheat during 2012/13 and 2014/15 harvest seasons, respectively, were identified as belonging to the Fusarium graminearum species complex. PCR assays were used to differentiate the 15-acetyldeoxynivalenol (15-ADON), 3-acetyldeoxynivalenol (3-ADON) and nivalenol (NIV) genotypes. The trichothecene type B chemotype, zearalenone, and NX-2 toxin profiles were determined based on chromatographic (LC-MS/MS) analysis. Differences in the genotype frequency were due to the target locus analyzed and year of isolation of the strain. The most common genotype and chemotype was 15-ADON in both seasons, but an increasing frequency of the 3-ADON chemotype was found in the non-epidemic season (2014/15). The strains were able to produce zearalenone and its masked derivatives, but not the type A trichothecene NX-2. This is the first report of the production of zearalenone and its modified mycotoxins by Fusarium graminearum species complex strains isolated from Argentina.